Geographical Distribution and Risk Association of Human Papillomavirus Genotype 52–Variant Lineages. (30th May 2014) - Zhang, Chuqing; Park, Jong-Sup; Grce, Magdalena; Hibbitts, Samantha; Palefsky, Joel M.; Konno, Ryo; Smith-McCune, Karen K.; Giovannelli, Lucia; Chu, Tang-Yuan; Picconi, María Alejandra; Piña-Sánchez, Patricia; Settheetham-Ishida, Wannapa; et al.
Abstract : Human papillomavirus (HPV) genotype 52 is commonly found in Asian cases of cervical cancer but is rare elsewhere. Analysis of 611 isolates collected worldwide revealed a remarkable geographical distribution, with lineage B predominating in Asia (89.0% vs 0%–5.5%; P corrected < .001), whereas lineage A predominated in Africa, the Americas, and Europe. We propose that the name "Asian lineage" be used to denote lineage B, to signify this feature. Preliminary analysis suggested a higher disease risk for lineage B, although ethnogeographical confounders could not be excluded. Further studies are warranted to verify whether the reported high attribution of disease to HPV52 in Asia is due to the high prevalence of lineage B.